Higher-Order or Critical Thinking Skills: Does Accounting Education Need Reforms? - Muhamad, Rusnah; Sulaiman, Noor Adwa (Asian Journal of Accounting Perspectives, 2013)
Various authors point out the repeated calls by stakeholders in the accounting profession for the development of enhanced critical skills in accounting graduates to ensure the long-term development of the profession. This paper discusses the importance of developing higher-order or critical thinking skills among accounting graduates prior to entering the job market. It identifies the two steps needed to improve accounting education, namely to recognise the need for change and to identify the specific changes needed. Critical thinking skills are needed to enable accounting graduates to cope not only with advancements in Information Technology, but also a competitive business environment in a globalised world economy.